Utilization of Local Wisdom as a Source of Social Studies Learning to Instill Cultural Values and Tolerance in SD/MI - L, Zulkhairiah Azahra; Harahap, Annisa Lestari; Azizah, Nurul; Hasibuan, Fifi Indriani; Amelia, Alya; Yusnaldi, Eka (Holistic Science, 2024)
This study aims to examine the use of local wisdom as a learning resource in Social Studies (IPS) learning to instill cultural values and tolerance in elementary school students. The study used a qualitative approach with a descriptive method. Data collection techniques included in-depth interviews with teachers and local community leaders, observation of the learning process in the classroom, and analysis of documents related to teaching materials and curriculum. Data were analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the integration of local wisdom into IPS learning can increase students' awareness of local cultural values while forming an attitude of tolerance towards cultural diversity in the surrounding environment. In addition, this strategy also provides a contextual learning experience that is relevant to students' daily lives. This study recommends the importance of training for teachers in developing local wisdom-based learning methods and compiling learning modules that are appropriate to the local context.